The relationship between body image and adjustment in breast cancer patients: The mediating role of self-compassion and psychological resilience - Mohammad Reza Tamannaeifar; Azam Mansourinik; Ezat Golestani (Fiyz̤, 2023)
Background: Breast cancer is the most common cancer in women and the first cause of cancer-related death among them. In the survivors of this cancer, several factors play a role in adapting to the disease. Therefore, the present study investigated the mediating role of self-compassion and psychological resilience in the relationship between body image and adjustment in breast cancer patients. Materials and Methods: The method of the current study was structural equation modeling. The statistical population included all women with breast cancer undergoing treatment at Ayatollah Yathrabi Hospital in Kashan, Iran, in 2022. A total of 202 patients were selected using the convenience sampling. Data were collected using the Body Image Scale, Self-compassion Scale-short form, Resilience Scale-short form and Psychosocial adjustment to illness scale. Then, the data were analyzed by AMOS 24. Results: The results of direct paths showed that the effect of body image on self-compassion and psychological resilience was significant (P<0.01). Moreover, the effect of self-compassion and psychological resilience on psychosocial adjustment to the disease was significant (P<0.05). The results of Indirect paths indicated that self-compassion and psychological resilience completely mediated the relationship between body image and psychosocial adjustment to the disease (P<0.01). Conclusion: The self-compassion and resilience can be useful for increasing the psychosocial adjustment of breast cancer survivors. Future studies in more diverse samples are needed to confirm the causal direction of these relationships and extend the findings.